The Effectiveness of Short-Video Social Media Advertising: A Case Study of Tik Tok And Kwai In China - Gao, Tiannan (2019)
As a kind of new industry, short video social service allows users to record their lives and experience and upload these videos to their short video social accounts. There are two main short video social service platforms in China: Tik Tok and Kwai. Advertising on short video platforms is generally regarded as an effective marketing strategy in China as the huge user base they have. However, the academic studies in this industry are less than market researches. This paper will discuss the effects of advertising on the short video industry based on the Theory of Planned Theory and figure out the most effective predictor that influencing consumer purchase intention in this area. It will be concluded that the combination of multiple tactics will be the most effective marketing strategy and the most significant factor is the internalization of the subjective norms.